Presence and antibiotic resistance of salmonella spp. isolated from chicken meat and giblets consumed in konya, turkey - Arife Ezgi Telli; Yusuf Biçer; Hatice Ahu Kahraman; Nihat Telli; Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
Aim: The present study was on the detection of Salmonella spp. and two important Salmonella serotypes (S. Thyphimurium and S. Enteritidis) in chicken meat and giblets and also determination of antimicrobial resistance of the isolates. Materials and Methods: In this study, livers (n=40), gizzards (n=40), hearts (n=30), skins (n=30), drumsticks (n=10) and wings (n=20) were collected from supermarkets and butcher shops in Konya, Turkey. The samples were analyzed by Classical Cultural Technique. Molecular confirmation of the suspicious colonies was carried out using Inv-A gene- based PCR. Flic-C and IE-1 primers were used by duplex PCR for S. Thyphimurium and S. Enteritidis respectively. Antibiotic resistance of the isolates was determined by the disk diffusion method. Results: Forty-three (25.29 %) of 170 samples were positive for Salmonella spp. According to the d-PCR assay, neither S. Thyphimurium nor S. Enteritidis was not detected. The resistance to clindamycin, oxacillin, teicoplanin were evident 100 % and resistance to vancomycin (79.1